School victimization and Internet addiction among Chinese adolescents: The mediating roles of life satisfaction and loneliness - Shi, Xinxin; Wang, Rulin (Frontiers in Psychology, 2023)
The present study investigated the possibility of life satisfaction and loneliness mediating the link between school victimization and Internet addiction. A total of 3,363 middle/high school students (45% males; Mage = 15.67 years old, SD = 1.58) completed a series of self-report questionnaires, which included school victimization, life satisfaction, loneliness, and Internet addiction. The findings demonstrated a positive relationship between school victimization and Internet addiction. In addition, life satisfaction and loneliness mediated the link between school victimization and Internet addiction. Overall, these findings contribute to a better understanding of the association between school victimization and Internet addiction. They also extended the GST, providing suggestions for preventing and managing adolescents’ Internet addiction.